Knowledge, attitude and reception of patients with squamous cell carcinoma of the conjuctiva on the importance of HIV testing at Queen Elizabeth Central Hospital. - Kamzunzeni, Mainess (Kamuzu University of Health Sciences, 2022)
The cancer of the conjunctiva is one of the common conditions treated at QECH eye department. The association between cancer of the conjunctiva and HIV is well documented in literature. Cancer of the conjunctiva can cause visual impairment and blindness. The purpose of the study is to explore the knowledge, attitude and perception of patients with cancer of the conjunctiva on the importance of having an HIV testing at Lion's First Sight Eye Unit at Queen Elizabeth Central Hospital in Blantyre Malawi. The study will be an exploratory Qualitative in nature and a sample will be selected using convenience sampling and an interview guide will be used to collect data. The Health Belief Model will be used to provide a frame work for the study.